STRATEGI USAHA MIKRO KECIL MENENGAH (UMKM) DALAM PEMBERDAYAAN MASYARAKAT (STUDI PADA SENTRA KERUPUK DI DESA JAMBANGAN) - Desy Triana Afdillah; Ilmi Usrotin Choiriyah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to find out and describe the Strategy of Micro, Small and Medium Enterprises (MSMEs) in Community Empowerment (Study on the Cracker Center in Jambangan Village). This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. The determination of the informants of this research was through purposive sampling consisting of the Head of Hamlet who is responsible for community empowerment in the field of MSMEs and several Cracker MSME actors. Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that the strategy of Cracker MSMEs in Jambangan Village is still not running as expected, because the marketing aspect is still manual. This is due to the lack of use of digital platforms as a promotional medium which limits market reach. In addition, less attractive product packaging negatively impacts sales, as prominent packaging can attract consumer interest. This is the main factor in hindering the success of the Cracker MSME strategy in Jambangan Village.